Exceptionally low thermal conductivity realized in the chalcopyrite CuFeS2 via atomic-level lattice engineering. (April 2022) - Ge, Bangzhi; Lee, Hyungseok; Zhou, Chongjian; Lu, Weiqun; Hu, Jiabin; Yang, Jian; Cho, Sung-Pyo; Qiao, Guanjun; Shi, Zhongqi; Chung, In
Abstract: Designing irregular but desirable atomic arrangements in crystal lattices of solids can greatly change their intrinsic physical properties beyond expectations from common doping and alloying. However, structures of solids are generally determined by thermodynamic preferences during solid-state reactions, strictly restricting delicate atomic-level lattice engineering. Here, we report a new strategy of realizing desirable defect architecture in a highly predictable way to control thermal and charge transport properties of solids. Introducing unusually high concentration indium to the tetragonal chalcopyrite CuFeS2 to form the Cu1− x In x FeS2 ( x = 0–0.12) system stabilizes the highly unusual local structure, namely, high-temperature polymorph of cubic zinc blende structure in the surrounding matrix and displaced In + cation with 5s 2 lone pair electrons from the Cu + sublattice. This substantially suppresses notoriously high lattice thermal conductivity of tetrahedrally networked CuFeS2 to record-low values 0.79 W m −1 K −1 at 723 K through multiscale scattering and softening mechanisms of heat-carrying phonon, approaching its theoretical lower limit. Consequently, one of the highest thermoelectric figures of merit, ZT, among chalcopyrite sulfides is achieved. Our design principle utilizes standard potentials and ionic radius of constituent elements, thereby readily applicable to designing various classes of solids. Remarkably, we directly imaged the atomic-level structure of positional disorder stabilizing the high-temperature phase and off-centered In + from the ideal position employing a scanning transmission electron microscope. This observation shows how our material design strategy works, and provides important understanding for how local structures in solids form when either compatible or incompatible atoms are introduced to the crystal lattices. Graphical Abstract: ga1 Highlights: Design of atomic-level lattice engineering by thermodynamic consideration. High-temperature polymorph for chalcopyrite is unprecedentedly stabilized at RT. Direct observation of atomic-level defect structures. Severe positional disorder coupled with phonon softening reduces κ L dramatically. Record-low κ L for chalcopyrite sulfide is achieved at 0.79 W m −1 K −1 .